Osteology of Viavenator exxoni (Abelisauridae; Furileusauria) from the Bajo de la Carpa Formation, NW Patagonia, Argentina. (March 2018) - Filippi, Leonardo S.; Méndez, Ariel H.; Gianechini, Federico A.; Juárez Valieri, Rubén D.; Garrido, Alberto C.
Abstract: The complete osteology of the abelisaurid Viavenator exxoni, from the Bajo de la Carpa Formation (Santonian, Upper Cretaceous) is described. Viavenator is characterized by a series of autapomorphies, including: transversely compressed parietal depressions on both sides of the supraoccipital crest; ventral edges of the paraoccipital processes located above the level of the dorsal edge of the occipital condyle; basioccipital-opisthotic complex about two and a half times the width and almost twice the height of the occipital condyle, in posterior view; well-developed crest below the occipital condyle, diverging ventrally and defining the subcondylar recess; deeply excavated and sub-circular basisphenoidal recess, with its major axis transversely oriented; basipterygoid processes horizontally placed with respect to the cranial roof and located slightly dorsally to the basal tubera; mid and posterior cervical centra with slightly convex lateral and ventral surfaces; hyposphene-hypanthrum articular complex present from dorsal 2 onward; presence of an interspinous accessory articular system in middle and posterior dorsal vertebrae; presence of a pair of pneumatic foramina within the prespinal fossa in anterior caudal vertebrae; distal end of the scapular blade posteriorly curved. Particularly, Viavenator shows plesiomorphic cranial characters, i.e. flat frontals lacking domes or horns, combined with derived postcranial characters, e.g. the interspinous accessory joint system of dorsal vertebrae. This combination between plesiomorphic and derived traits suggests that Viavenator is a transitional form, which is an idea supported by its intermediate stratigraphic and phylogenetic placement between the basal and older (e.g. Skorpiovenator, Ilokelesia ) and derived and younger members of the clade (e.g. Aucasaurus, Carnotaurus ).